Beliefs and Attitudes in Women with Gestational Diabetes Mellitus. A Systematic Review (Global Journal of Medical Research, 2023)
Introduction The purpose of this research is to review systematic review of the most significant studies on the belief system and attitudes of pregnant women diagnosed with Diabetes Mellitus Gestational GDM within the framework of the psychosocial dimensions of this condition Materials and methods A systematic review based on the PRISMA methodology in PubMed Medline Scielo Hindawi Springer Link and BMC Medicine and inclusion and exclusion criteria were defined Results 207 papers were found to whom the abstract was reviewed after duplicates were discarded leaving 180 articles to which the inclusion and exclusion criteria were applied and 28 articles were selected at the end that provided relevant information for the objectives of the study study Results found allow us to infer the presence of a belief system around the consequences of gestational diabetes for pregnant women and their babies
Keywords: beliefs; attitudes; gestational diabetes mellitus; systematic review